Contraceptive Use among Reproductive Aged Women of Squatter Slum Areas in Surkhet Valley - Bohara, Kul Bahadur (Journal of Educational Research and Innovation, 2024)
This paper examines contraceptive use among reproductive aged women of squatter slum areas in Surkhet valley. Nepal has experienced a dramatic increase in contractive use. Fertility rate is a decline in Nepal. The main objective of the study was to examine the socio-demographic background of squatter slum women regarding contraceptive use and to find out the status of contraceptive use. The currently married women of reproductive age (15-49) were interviewed by applying systematic random sampling method without replacement. Sample size was 142 reproductive aged women. Despite intensive efforts from various sectors it is reducing in desirable level. Various studies suggest that fertility is found to be high especially in backwards communities. Squatter slum areas are one of the examples. An attempt is made in this study to find out the general features of these settlements mainly level of contraceptive use and its relation with some selected socio-economic variables. Definitely, environment condition of these settlements is found hazardous. The family planning program in Nepal has been considered a success in a setting without much socio-economic development. With the concerted effort of the government of Nepal and Non-governmental Organizations (INGOs), women are becoming aware of physical health. Contraception prevalence level is not found satisfactory. About half of the eligible couple out of total couples is yet to contraceptive use. Age of the user, age at marriage, child ever born, husband’s education, women’s education and working status of spouse are positively correlated with the contraceptive use.